2012
DOI: 10.4137/cmo.s7654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of TroVax in the Treatment of Progressive Castration-resistant Prostate Cancer

Abstract: With approximately 240,890 new cases expected in 2011, prostate cancer remains the leading cause of non-melanoma cancer deaths in men. Immunotherapies using viral vector-based delivery systems targeting tumor-specific antigens are being studied. Viral vector-based delivery systems present tumor-targeted antigens (TAAs) to the immune system while breaking self-tolerance. Modified vaccinia ankara has been combined with the oncofetal antigen 5T4 to create TroVax for the treatment of castration-resistant prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…No serious adverse events were reported, the majority of the patients developed antibody and cellular responses to 5T4, and these responses correlated with clinical benefit, with tumor regression observed in some cases. TroVax has also been evaluated in clinical trials for treatment of castration resistant prostate cancer [59] and a phase III trial for renal carcinoma [60] in which no efficacy was observed. Attention is now focused on identifying subgroups of patients who may benefit from therapy with TroVax [61].…”
Section: Use Of Recombinant Mva To Induce T Cell Responses In Other Vmentioning
confidence: 99%
“…No serious adverse events were reported, the majority of the patients developed antibody and cellular responses to 5T4, and these responses correlated with clinical benefit, with tumor regression observed in some cases. TroVax has also been evaluated in clinical trials for treatment of castration resistant prostate cancer [59] and a phase III trial for renal carcinoma [60] in which no efficacy was observed. Attention is now focused on identifying subgroups of patients who may benefit from therapy with TroVax [61].…”
Section: Use Of Recombinant Mva To Induce T Cell Responses In Other Vmentioning
confidence: 99%
“…For example, vaccines can be used to train the immune system to selectively destroy cancer cells. Unfortunately, the responses vaccines elicit may require months to mature and are usually insufficient to control advanced disease (2)(3)(4)(5). In an effort to increase vaccine potency, various adjuvant compounds that stimulate tumor antigen uptake and cross-priming of naive T cells have been developed, and an understanding of innate signaling mechanisms has made it possible to rationally design more precise immunostimulants for treating cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To date, immunotherapy represents an appealing option in prostate cancer treatment [12]. The FDA-approved vaccine (sipeucel-T [13]) and PD-1 inhibitor (e.g., pembrolizumab [14]) have been used to treat advanced PCa in clinical trials. However, recent phase III trials showed multiple failures of immunotherapy in PCa [1518].…”
Section: Introductionmentioning
confidence: 99%